Trainee psychotherapists’ emotion recognition accuracy improves after training: emotion recognition training as a tool for psychotherapy education - Döllinger, Lillian; Högman, Lennart Björn; Laukka, Petri; Bänziger, Tanja; Makower, Irena; Fischer, Håkan; Hau, Stephan (Frontiers in Psychology, 2023)
Psychotherapists’ emotional and empathic competencies have a positive influence on psychotherapy outcome and alliance. However, it is doubtful whether psychotherapy education in itself leads to improvements in trainee psychotherapists’ emotion recognition accuracy, which is an essential part of these competences. In a randomized, controlled, double-blind study (N = 68), we trained trainee psychotherapists (57% psychodynamic therapy and 43% cognitive behavioral therapy) to detect non-verbal emotional expressions in others using standardized computerized trainings – one for multimodal emotion recognition accuracy and one for micro expression recognition accuracy - and compared their results to an active control group one week after the training (n = 60) and at the one-year follow up (n = 55). The participants trained once weekly during a three-week period. As outcome measures, we used a multimodal emotion recognition accuracy task, a micro expression recognition accuracy task and an emotion recognition task for verbal and non-verbal (combined) emotional expressions in medical settings. The results of mixed multilevel analyses suggest that the multimodal emotion recognition accuracy (ERA) training led to significantly steeper increases than the other two groups from pretest to the posttest one week after the last training session. When comparing the pretest to follow-up differences in slopes, the superiority of the multimodal training group was still detectable in the unimodal audio modality and the unimodal video modality (in comparison to the control training group), but not when considering the multimodal audio-video modality or the total score of the multimodal ERA measure. The micro expression training group showed a significantly steeper change trajectory from pretest to posttest compared to the control training group, but not compared to the multimodal training group. However, the effect vanished again until the one-year follow-up. There were no differences in ERA trajectories for the outcome measure about ERA in medical settings. We conclude that trainee psychotherapists’ emotion recognition accuracy can be effectively trained, especially multimodal emotion recognition accuracy and at least in the short term, and that the changes in unimodal ERA (audio-only and video-only) are more long-lasting. Implications of these findings for the psychotherapy education are discussed.